PUBLIC SERVICE INNOVATION AT THE MINISTRY OF RELIGIOUS AFFAIRS PANGANDARAN: ENHANCING MARRIAGE, WAQF, AND HAJJ SERVICES IN 2024 - Yeti Rohayati; Tati Sarihati; Shinta Dzauharoh (Al-Mubin, 2025)
This study examines public service innovation in marriage, waqf, and hajj services at the Ministry of Religious Affairs of Pangandaran Regency in 2024. The study responds to the urgent need to improve religious public services amid high service pressure, administrative complexity, and increasing demands for accessible, efficient, and reliable delivery. Drawing on public service innovation, public service logic, and service quality perspectives, it identifies the forms of innovation implemented and explains their implications for access, efficiency, and service certainty. A qualitative case study was employed using document analysis and secondary data from institutional performance records and official service platforms. The findings show that innovation operates through process digitalization, administrative structuring, service access expansion, and information management across the three services. These innovations strengthen institutional capacity by improving procedural order, data accuracy, legal certainty, and transparency, while also offering a broader integrated institutional reading of religious public service innovation at the local level